Attachment style as a determinant of romantic partner choice - Frankova Ірина; Gavrilova Оксана (Psychosomatic Medicine and General Practice, 2020)
Relationships in society meet different social needs, for example, belonging to a social group (friends, neighbours) is needed to ensure a sense of social integration, and attachment (for example, in a romantic couple) is needed to meet the need for emotional intimacy. One of the important tasks of late adolescence is to establish an intimate relationship with a romantic partner. It is known that an important predictor of partner choice is the early experience of attachment to parents. The system of attachment is a critical component in human relations. This experience will affect personality and interpersonal relationships in the later stages of ontogenesis. The article presents a literature review, both theoretical and empirical studies, of the links between attachment to a romantic partner and features of relationships with parents. The dependence of the quality of attachment to a romantic partner with the quality of attachment to parents was determined. The quality of attachment to parents correlates with the image of them and their attitude to sons and daughters. Features of attachment to a romantic partner are associated with the images of both the parents and the partner. Without a reliable attachment base, the processing of emotionally charged conflicts from the past between partners is almost impossible, without this base activated fears and anxieties often become unbearable for the couple, a lot of resistance occurs. The concept of transferring the style of attachment between generations proves that people who lack confidence in their parents, as adults, have difficulties in establishing stable romantic relationships and empathic response to the needs of their children. Therefore, studying the factors and mechanisms of the attachment system development in adolescence with possible further psychotherapeutic influence is of particular importance for psychology in general, and medical psychology in particular.